The Role Of English In The Development Of Islam In Indonesia - Aizan Yaacob; Gumarpi Rahis Pasaribu (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2024)
English plays an important role in the development of Islam in Indonesia, especially in the era of globalization. This study aims to explore how English is used in Islamic education, digital da'wah, and academic literature to support the development of Islam. A descriptive qualitative approach was used by collecting data through interviews, observations, and documentation in Islamic educational institutions, digital da'wah communities, and academics. The results of the study indicate that English has become an integral part of Islamic education, especially in modern Islamic boarding schools and Islamic universities, in order to prepare a generation of Muslims who are able to compete globally. In digital da'wah, English is used to convey Islamic values to international audiences in an inclusive and modern way. Meanwhile, Islamic literature in English produced by Indonesian academics contributes to the global discourse on moderate Islam. However, challenges remain, including gaps in English language competency, limited access to literature, and concerns about shifting local identities. This study suggests strategies, such as English language training for educators and da'wah, integrated curriculum development, and increasing the distribution of Islamic literature in English. With these strategic steps, English can be optimally utilized to strengthen the role of Indonesian Islam in the global arena without sacrificing local identity.